How to finish and defend your dissertation strategies to complete the professional practice doctrine - Grant, Cynthia; Tomal, Daniel R. (Rowman & Littlefield Education, 2013)
A first of its kind, this book provides you everything you need to know about successfully passing the dissertation defense such as: preparing and finishing the manuscript, using cloud-based communities, preparing presentations, using effective communication strategies, managing stress, motivating yourself, revising and editing the manuscript, publishing and presenting the final dissertation and more.